Association Between Hypoxia‐Inducible Factor‐1α and Neurological Diseases: A Bidirectional Two‐Sample Mendelian Randomization Analysis - Jing Liang; Xiaoyan Du; Mengfei Wang; Hongqin Zheng; Yang Sun; Yi Lin (Brain and Behavior)
ABSTRACT Background Previous studies have suggested that hypoxia‐inducible factor 1‐α (HIF‐1α) exerted multiple effects on different central nervous system disorders. However, it is still uncertain whether plasma HIF‐1α can be a causal indicator for the relevant diseases. This study aimed to test the causality relationship between plasma HIF‐1α and neurological diseases, including cerebrovascular diseases, migraines, and neurodegenerative diseases with a Mendelian randomization (MR) method. Methods Single‐nucleotide polymorphisms (SNPs) genetically representing plasma HIF‐1α were screened as instrumental variables (IVs). Summary‐level data for neurological disorder from genome‐wide association studies (GWAS) were identified as outcomes. The causal effects between the IVs and outcomes were determined via the major analysis of inverse‐variance‐weighted (IVW) method. The reverse causal direction was also performed to investigate the possibility of reverse causation. Results The findings revealed that plasma HIF‐1α was identified to be genetically associated with cardioembolic stroke (CES) (OR = 0.885; 95% confidence interval [CI] = 0.796–0.985, p = 0.026), migraine (OR = 0.941, 95% CI = 0.888–0.998, p = 0.041), and drug‐induced migraine without aura (MOA) (OR = 0.586, 95% CI = 0.375–0.916, p = 0.019). There was no association identified in plasma HIF‐1α with subarachnoid hemorrhage (SAH), other stroke and migraine subtype, and neurodegenerative disorders. The reverse‐MR analysis revealed that the above‐stated neurological diseases did not have a causal effect on plasma HIF‐1α levels. Sensitivity and validation analyses support that the above results are stable. Conclusions Our research indicated that plasma HIF‐1α may have a causal effect on the risk of CES, migraine and drug‐induced MOA, providing new insights for those disease prevention and therapeutic approaches.